190: ENDOSCOPIC SUBMUCOSAL DISSECTION (ESD) AND ROBOTIC SENTINEL NODE NAVIGATION SURGERY FOR EARLY GASTRIC CANCER: FIRST EXPERIENCE AND PRELIMINARY RESULTS. (23rd April 2022) - Bottari, A; Fortuna, L; Coratti, F; Cianchi, F; Staderini, F
Abstract: Background and aim: Early gastric cancer (EGC) is defined as a cancer limited to mucosa (T1a) and submucosa (T1b). The 5-year survival rates are respectively 96% and 83% for T1a and T1b. Despite endoscopic submucosal dissection (ESD) is considered the standard treatment for EGC, literature reports a quite considerable rate of lymph-node metastasis (2% to 18%). Combined surgical-endoscopic treatment can achieve accurate resection of EGC, solving the problem of lymphadenectomy which cannot be performed endoscopically. Near infrared (NIR) fluorescence imaging with indocyanine green (ICG) was recently introduced for lymphatic mapping in several tumors. The aim of the study is to evaluate the feasibility and safety of ESD in combination with robotic ICG guided sentinel node navigation surgery (SNNS). Methods: ICG was endoscopically injected intraoperatively into the submucosal layer around the tumor. Intraoperative NIR imaging with ICG was carried out with a near-infrared camera system built into the robotic platform. The first lymph node which had taken up ICG appeared as a green spot and was identified as the sentinel node (SN). SN was then sent for extemporaneous histopathological examination. When ICG fluorescence extended to the second nodal stations a ICG guided robotic basin lymphadenectomy was performed. Basin lymph nodes were sent for definitive histopathological analysis. If no tumoral cells were identified in the SN, an ESD with standard technique was conducted. If the SN pathological examination revealed tumoral cells, a robotic radical resection and D2 lymphadenectomy was completed. Results: Seven ESDs with SNNS and basin lymphadenectomy basin were performed. No gastric perforations or other intraoperative complications were registered. Mean operative time was 148.6 minutes. All the procedures histologically resulted in complete excisions. No lymph nodes metastasis was demonstrated in either the SN or the basin lymph nodes. A mean of 12 lymph-nodes was collected. Mean hospitalization time was 2.8 days. Conclusion: In our preliminary experience, combined ESD and SNNS could be recommended as a safe and effective treatment for EGC in patients with potential risk of LN metastasis or in patients with multiple comorbidity in order to avoid more invasive organ resections.